Energy-saving analysis of air source heat pump integrated with a water storage tank for heating applications. (August 2020) - Wu, Pin; Wang, Zhichao; Li, Xiaofeng; Xu, Zhaowei; Yang, Yingxia; Yang, Qiang
Abstract: Due to declining fossil fuel reserves and environmental contamination, the use of air source heat pumps has become a significant alternative to fossil fuel heating. In this paper, a heating system using an air source heat pump integrated with a water storage tank was constructed, to improve the operating efficiency of the air source heat pump (ASHP) at low ambient temperatures. It ran under a novel operation strategy of ASHP heating and water storage tank charging during the daytime, ASHP switching off and the water storage tank discharging at night. Under this approach, the ASHPs always operated at higher ambient temperatures and switched off at lower ambient temperatures. The test system of the air source heat pump integrated with a water storage tank was installed and monitored long-term in a practical building in Beijing. According to the monitored data from December 1st, 2018 to March 11th, 2019, the daily average ambient temperature varied from −9.3 °C to 11.3 °C, while the daily average indoor temperature ranged from 21.0 °C to 23.0 °C. The ASHP's daily average coefficient of performance (COP) on the coldest day was 2.35, and the seasonal coefficient of performance (SCOP) was 2.95. As compared to the continuous operation mode, the ASHP's daily average COP was enhanced by 14.0% on the coldest day, and the SCOP has improved by 26.1%. The air source heat pump integrated with a water storage tank has significant energy-saving potential under this operation strategy. Highlights: An integrated ASHP heating system was constructed in a novel operation strategy. The system was monitored by multiple measuring points and sensors for 78 days. The measured SCOP of ASHP was 2.95, improved by 26.1% to traditional mode. Daily COPs enhanced by 14.0%–42.9% with different ambient temperatures. Defrosting duration and electrical energy consumption were quantitatively analyzed.